Clinical and financial impacts of flexible intramedullary nailing in pediatric diaphyseal forearm fractures: A case–control study. (June 2022) - Leuba, Aline; Ceroni, Dimitri; Tabard-Fougère, Anne; Lutz, Nicolas
Purpose: Flexible intramedullary nailing is regularly applied for pediatric displaced unstable forearm fractures. When compared to closed reduction and casting (orthopedic treatment), flexible intramedullary nailing decreases malalignment, shortens immobilization time, and should decrease follow-up controls. Comparing flexible intramedullary nailing and orthopedic treatment in the clinical, radiological, and financial managements of these fractures was performed. Methods: Retrospective 5 years study of pediatric cases in two pediatric orthopedic university departments. Treatment method, post-operative course, and radiological follow-up were reviewed. Number of radiographs, follow-up controls, type and duration of immobilization, final bone angulation, and reported complications were compared. Extensive financial analysis was completed. Results: Of 73 girls and 168 boys included in the study, 150 were treated by flexible intramedullary nailing and 91 by orthopedic treatment. No difference was noted with regard to total number of radiographs (7.3 vs 7.2, respectively). Total number of follow-ups was 6.4 and 5.5, respectively. Malalignment occurred in two flexible intramedullary nailing and sixteen orthopedic treatments. The least expensive cost was ambulatory orthopedic treatment. Conclusion: Flexible intramedullary nailing treated children had similar numbers of radiographs or follow-up consultation, but less malunion when compared to orthopedic treatment. Orthopedic management was systematically cheaper than flexible intramedullary nailing. Unless post-operative management guidelines decreasing the number of radiographs and follow-ups are implemented, flexible intramedullary nailing will remain a costly procedure when compared to conventional orthopedic treatment. Level of evidence: level III case–control retrospective study.